ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN NELAYAN DI KABUPATEN JEMBRANA - Kusuma, Dwi; Setiawina, I Nyoman Djinar; Utama, I Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This study aims to analyze the influence of social capital on income, analyze the factors of production to income, analyze the influence of social capital to the welfare of fishermen, analyze the influence of production factors to fisherman's welfare in Jembrana regency, and analyze the influence of social capital and production factors through income mediator to fisherman's welfare in Jembrana District. In this research use survey method by taking sample 98 responden from population of 4,876 people, with technique of descriptive statistical data analysis and analysis of SEM PLS. The results of testing in the study showed: 1) Social capital positively affects the income of fishermen; Factor of Production have positive effect to fisherman's income; 2) Social capital has a positive effect on fishermen's welfare in Jembrana Regency; Factor of Production have positive effect to fisherman's prosperity in Jembrana Regency; 3) Revenues mediate the influence of social capital and production factors on fishermen's welfare in Jembrana District.